Comparative Analysis of Psychophysiological and Health Indicators of Aged, Elderly and Long-Lived from Different Mountainous Districts of Azerbaijan - Karamova Natavan; Primkulova Sitora; Meyliyev Bakhtiyor (BIO Web of Conferences)
The presented article provides a comparative analysis of psychophysiological and health indicators of the aged, elderly and long- lived from different mountainous regions of Azerbaijan. Thus, Azerbaijan has historically been chosen as the land of centenarians and had the terrain in the center of attention. The influence of natural complex terrain on life expectancy is one of the most urgent problems in the scientific literature. The observational studies involved the aged (65-74 years old), the elderly (75-89 years old) and long-lived (90 years and older) from Kalbajar, Lachin and Zangilan districts, which are mountainous territories of Azerbaijan. The studies measured general anxiety, situational and individual anxiety, visual memory and attention, systolic and diastolic blood pressure, and heart rate in 1 minute. In a comparative analysis of the results obtained, again, people living in mountainous areas maintain their health indicators due to strong adaptive processes that allow them to reach the age of longevity, the psychophysiological indicators of long-lived are within the normal range. Compared with the aged and the elderly, low and average levels of anxiety were revealed, visual memory and attention were higher than normal and higher health indicators. A comparative analysis of the results obtained showed that the physiological processes of the inhabitants of high-altitude areas were within the normal range. Kalbajar and Lachin districts are the most mountainous regions, while the Zangilan district is the middle and lower mountainous area. A comparison of the results obtained generally showed that the psychophysiological and health indicators of elderly in Zangilan district differ more sharply from the norm and increase the incidence of neuropsychiatric and somatic diseases.